Men and the Responsibility of Restoring Women's Glory Perspective of Mutawalli Al-Sya'rawi in the Book of Tafsir Al-Mar'ah fĭ Al-Qur'ān Al-Karĭm - Rifdi, Moh (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
Acts of violence against women such as domestic violence (KDRT), harassment and other forms of violence are caused by the majority of men considering and positioning themselves as nobler and stronger than women. Many studies discuss men, women and gender equality from various points of view. However, research that emphasizes the full responsibility of men towards women from an interpretive perspective is still rare. This article aims to outline a discussion about men's responsibilities in maintaining and restoring the glory of women which is declining amidst the times. By using a contextual-based interpretive approach, this researcher explores the interpretation of Surah Al-Rūm verse 21 from Mutawalli Al-Sya'rawi's perspective in describing the significant roles of men and women. This research shows that men as human beings who are given superior strength and a higher status than women have the full responsibility throughout life to care for and glorify women both inside and outside the bonds of marriage, especially to restore the glory of women who are currently experiencing decline amidst the times. This study is useful as additional knowledge and theory to help awareness of the magnitude of men's responsibility in looking after women anytime and anywhere